'It Was All a Big Theatre': Velvet revolutions, ethnic conflicts, and conspiracy theories in Eastern Europe. (November 2015) - Haluzík, Radan
In 1989 mass democratic – and later nationalist – movements rose up against governments in Eastern Europe and all communist regimes fell like overripe pears. The very speed and ease of this collapse gave rise to speculations and conspiracy theories in the general public, as well as among those who had taken part in the movements themselves. Why did this all happen at once – so suddenly, why did it all go so smoothly, and who organized it all…?! The "staging" of the democratic revolutions (Central Europe) and their subsequent national ethnic conflicts (Yugoslavia, post-Soviet Caucasus), was blamed on diverse causes: the dark political forces of USA, Russia, EU, Germany, international capital, power-hungry politicians, the secret police, and so forth… In this article I wish to record my own experience, as a student activist during the Czechoslovak Velvet Revolution, and as a social anthropologist and war journalist working for several years during the ethnic wars in Yugoslavia and in the Post-Soviet Caucasus. I address the main reasons that prevented understanding the post-communist mass movements and open a space to popular myths and conspiracy theories: 1. tendencies to political theatre, 2. spontaneity and self-organization of mass movements, 3. "mass intoxication" and the internal transformation of the ecstatic actor – activist. Exploring question marks and speculations about these key moments of these mass movements contributes to their understanding.